The Influence Of Extracuricular Sports Programs On The Development Of Life Skills During The Covid-19 Pandemi At Ta'mirul Islam Elementary School - Prima Ayu Sukarsana Wijayanti; Pipit Pitriani; Agus Mahendra (STKIP Muhammadiyah Kuningan, 2023)
The purpose of this research is to explore life skills that are developed through sports at the Ta'mirul Islam Elementary School in Surakarta. More in-depth research is needed to explore the role of developing life skills through sports extracurricular participation. Data was collected through the Life Skills Scale for Sport (LSSS) and supporting questionnaires using survey techniques. The research method used is descriptive-comparative causal (expose facto). The results showed (1) students who took part in sports extracurriculars obtained the highest life skills; (2) there are differences in the value of life skills between groups of students who take part in sports extracurriculars and groups of students who take part in non-sport extracurriculars; (3) there are differences in the values ​​of life skills between groups of students who take part in sports extracurriculars and groups of students who do not take part in any extracurriculars; (4) There are differences in the values ​​of life skills between groups of students who take part in non-sport extracurriculars and groups of students who do not take part in any extracurriculars. Conclusion sports extracurriculars can be used by schools as a means to transfer life skills to students in order to develop all the potential that exists in students to live their daily lives.